Differential synovial tissue expression of TLRs in seropositive and seronegative rheumatoid arthritis: A preliminary report - Alzahraa Abdelwahab; Sanna Palosaari; Soha Abdelkawy Abdelwahab; Rehab Ahmed Rifaai; Nashwa Fathy El-Tahawy; Entesar Ali Saber; Tomi Nousiainen; Maarit Valkealahti; Johanna Huhtakangas; Tuomo J. Karttunen; Petri Lehenkari (Taylor & Francis Group, 2021)
Toll-like receptors (TLRs) are known to have an important role in triggering the innate immune response and in priming antigen-specific adaptive immunity and inflammation. The differences in synovial tissue expression of the TLRs between seronegative and seropositive rheumatoid arthritis (RA) were examined from 9 seropositive RA, 5 seronegative RA and 4 osteoarthritis (OA) patients. Synovitis status was assessed using Krenn's scoring and TLR 1-9 expression by immunohistochemistry. Tissue citrulline content was analysed by HPLC method. In RA TLR expression was generally higher than in OA. TLR2 expression was higher in both seronegative and seropositive RA compared to OA. TLR 1, 4 and 8 expressions were higher in seropositive RA than in seronegative RA or in OA. For TLRs 3, 5, 6, 7 and 9 local differences of expression were found between groups. TLR 1-9 expression correlated with the synovitis grade. No statistical difference was found in synovial tissue citrulline content between the groups. In seropositive RA, the TLR repertoire in the synovial tissue differs from seronegative RA and could explain differences in disease outcomes. The high expression of protein sensing (TLR1, TLR2 and TLR4) and nucleic acid sensing TLRs (TLR7, TLR8 and TLR9) in the seropositive RA could make the synovium primed for reacting to citrullinated proteins and nucleic acids that could be released to extracellular space in formation of neutrophil extracellular traps. This reactivity could be augmented by Fc receptor activation by anti-citrullinated protein antibody immunocomplexes associated with seropositive RA.